HUBUNGAN ANTARA KEMAMPUAN BERPIKIR LOGIS DAN PENGETAHUAN TENTANG PARAGRAF DENGAN KETERAMPILAN MENULIS ESAI BAHASA INGGRIS - Siahaan, Leroy Holman (Sosio Religi: Jurnal Kajian Pendidikan Umum, 2016)
This research was aimed at finding out correlation between logical thinking ability and English essay writing skill, the knowledge of paragraph and English essay writing skill, and logical thinking ability together with the knowledge of paragraph towards English essay writing skill. This correlation research was conducted at grade XI SMA 71, East Jakarta. The used methods for this research were quantitative and survey. The population is XI graders who have English subject since they were at X grade. The sample was 10% from the population selected through simple random sampling method. To find out the correlation and regression among the variables,  EXCEL and SPSS software were technically used. The findings indicates that there is a positive relationship between logical thinking ability and English essay writing skill, a positive relationship between the knowledge of paragraph and English essay writing skill, and also a positive relationship together logical thinking ability, the knowledge of paragraph towards English essay writing skill.